Overview of promising manufacturers in the oil and gas sector of the Republic of Kazakhstan. - Z. A. K. B. B. O. Akhmetova Alikbaeva Zhaksygulova (Хабаршысы. Экономика сериясы, 2016)
The oil and gas sector of Kazakhstan at this stage is a key factor of development and has a major role in the socially and economically formation of regions. Due to the increasing importance of this sector will be relevant to consider the scope of the accompanying segment of oil and gas equipment, which is closely related to such processes as the production, processing and transportation of oil and gas. Currently in the domestic market of industrial equipment for the oil and gas operating large industrial facilities for the production of a wide range of oil and gas equipment, but there is a problem of low competitiveness with imported counterparts as a result of a lower quality, inadequate technological characteristics and the lack of marketing in these enterprises. In this regard, this paper provides an overview of the major domestic manufacturers and presents the prospects for the development of their activities.